HUKUM PROGRESIF SEBAGAI ALTERNATIF HUKUM YANG IDEAL - muhammad akbar (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2021)
This paper comes up with the idea that to implement the values of justice concerning law enforcement, the paradigmatic transformation from legal positivism to legal progressivism is highly needed. This is because the paradigm of legal progressivism contains compassion, empathy, determination, which are the indicators that contribute to promoting a sense of justice for the community. The historical record of law enforcement in Indonesia has known several names of law enforcers who have made progressive breakthroughs in overcoming the positive legal deadlock, for example, Bismar Siregar, Adi Andoyo Sutjipto, Asikin Kusumaatmadja (Judge); Baharudin Lopa (Prosecutor); Hoegeng (Police) and others. The solution offered in grounding the idea of progressive law is to make it a progressive legal movement.